The Influence of Animated Video Learning Media on Results Learning Geography for Class XI Students of SMA Negeri 6 Sidenreng Rappang - Nurfadillah; Usman M; Syamsunir; Sam Hermansyah (International Journal of Sustainable Applied Sciences, 2024)
The purpose of this influence study is to ascertain how animation-based video learning materials affect geography students in class XI of senior high school and country 6 Sidenreng Rappang. This study is quantitative in nature and employs a one-group pretest-posttest design with the Experimental Study method. The two variables in this study are the dependent variable, geography learning outcomes, and the independent variable, animation video learning media. There were 24 pupils in class XI IPS II at SMA Negeri 6 Sidenreng Rappang who made up the study's population. One pre-test and one post-test are given at the beginning and end of the class, respectively, as part of the data collection technique.  The hypothesis-taking test using the SPSS 25.0 application program used is the Wilcoxom Non-Parametric hypothesis analysis test . Study findings The significance of this display mark is 0.00 < 0.05. Mark Prior to testing The students' average score climbed from 38.33 to 86.66 on the post-test, indicating that their performance had improved. Calculated hypothesis using SPSS application software 25.0 For Windows, it may be inferred that the null hypothesis (H0) is rejected and the hypothesis work (H1) is accepted, indicating a significant difference in the social studies learning outcomes between the pretest and posttest. In light of this, the hypothesis that "Animated Video Learning Media Has an Influence on Class XI Learning Results at SMA Negeri 6 Sidenreng Rappang" was chosen.